Beneficial Effects of Lactic Acid Bacteria on Animal Reproduction Function - Mohamad Yusril Nur Mahendra; Tri Bhawono Dadi; Juriah Kamaludeen; Herinda Pertiwi (Veterinary Medicine International)
Considering the importance of a healthy uterus to the success of breeding, the beneficial effects of lactic acid bacteria on animal reproduction function are of particular interest. In recent decades, infertility has become a widespread issue, with microbiological variables playing a significant role. According to reports, dysbiosis of the vaginal microbiota is connected with infertility; however, the effect of the normal vaginal microbiota on infertility is unknown. In addition, lactic acid bacteria dominate the reproductive system. According to evidence, vaginal lactic acid bacteria play a crucial role in limiting the invasion of pathogenic bacteria by triggering anti-inflammatory chemicals through IL-8, IL-1, and IL-6; immunological responses through inhibition of the adherence of other microorganisms, production of inhibiting substances, and stimulation of mucus production; and also reproductive hormones by increased testosterone hormone release, enhanced the levels of luteinizing hormone, follicle stimulating hormone, the amount of prostaglandin E (2), and prostaglandin F2 alpha. The objective of this study was to compare the advantages of lactic acid bacteria in animal reproduction based on the most recent literature. The administration of a single strain or numerous strains of lactic acid bacteria has a favourable impact on steroidogenesis, gametogenesis, and animal fertility.